2018
DOI: 10.1186/s12870-018-1606-9
|View full text |Cite
|
Sign up to set email alerts
|

An APETALA1 ortholog affects plant architecture and seed yield component in oilseed rape (Brassica napus L.)

Abstract: BackgroundIncreasing the productivity of rapeseed as one of the widely cultivated oil crops in the world is of upmost importance. As flowering time and plant architecture play a key role in the regulation of rapeseed yield, understanding the genetic mechanism underlying these traits can boost the rapeseed breeding. Meristem identity genes are known to have pleiotropic effects on plant architecture and seed yield in various crops. To understand the function of one of the meristem identity genes, APETALA1 (AP1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 62 publications
3
19
0
Order By: Relevance
“…We found that B. rapa plants grown at 21°C started the floral transition around 24 days after germination (DAG), and quickly developed the first floral primordia (Figure a,b), whereas plants growing at 28°C showed a delayed formation of the inflorescence meristem, with some plants not starting floral transition (stages 1 to 2) up to 29 DAG (Figure a,b). In Arabidopsis, APETALA 1 / AGAMOUS LIKE 7 ( AP1 / AGL7 ) expression is a key marker for floral development (Andrés and Coupland, ) and, recently, mutations affecting a Brassica napus orthologue of this gene in chromosome A02 have been shown to alter plant architecture and flower morphology (Shah et al ., ). We monitored the temporal pattern of expression of the two closest B. rapa homologues to AP1 , BraA.AP1.a ( BraA07g030470.3C ) and BraA.AP1.b ( BraA02g018970.3C ), because these genes are upregulated during floral transition in pak choi ( Brassica rapa ssp.…”
Section: Resultsmentioning
confidence: 97%
“…We found that B. rapa plants grown at 21°C started the floral transition around 24 days after germination (DAG), and quickly developed the first floral primordia (Figure a,b), whereas plants growing at 28°C showed a delayed formation of the inflorescence meristem, with some plants not starting floral transition (stages 1 to 2) up to 29 DAG (Figure a,b). In Arabidopsis, APETALA 1 / AGAMOUS LIKE 7 ( AP1 / AGL7 ) expression is a key marker for floral development (Andrés and Coupland, ) and, recently, mutations affecting a Brassica napus orthologue of this gene in chromosome A02 have been shown to alter plant architecture and flower morphology (Shah et al ., ). We monitored the temporal pattern of expression of the two closest B. rapa homologues to AP1 , BraA.AP1.a ( BraA07g030470.3C ) and BraA.AP1.b ( BraA02g018970.3C ), because these genes are upregulated during floral transition in pak choi ( Brassica rapa ssp.…”
Section: Resultsmentioning
confidence: 97%
“…This seems to be also the case in rice, where overexpression of MADS15 resulted in reduced number of primary branches in the panicle (Lu et al, 2012). Similarly, a premature stop codon mutation in a homolog of AP1 in rapeseed altered plant architecture and increased the number of seeds per plant (Shah et al, 2018). Taken together, these results suggest that mutations in this group of meristem identity genes may be useful to modulate seed number in different plant species.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate that only multiple knockouts are useful in studying functionally redundant genes typical for polyploids. Although random mutagenesis was a common method to introduce new allelic variants into plant breeding, gene redundancy in rapeseed makes it challenging to reshape a trait by random mutagenesis (Braatz et al, 2018, Shah et al , 2018). Conversely, CRISPR‐Cas‐mediated genome editing enables multiple mutations simultaneously.…”
Section: Discussionmentioning
confidence: 99%